Superiority of Formalin-Fixed Paraffin-Embedded Brain Tissue for in vitro Assessment of Progressive Supranuclear Palsy Tau Pathology With [18F]PI-2620 - Willroider, Marie; Roeber, Sigrun; Horn, Anja K. E.; Arzberger, Thomas; Scheifele, Maximilian; Respondek, Gesine; Sabri, Osama; Barthel, Henryk; Patt, Marianne; Mishchenko, Olena; Schildan, Andreas; Mueller, André; et al. (Frontiers in Neurology, 2021)
Objectives: Autoradiography on brain tissue is used to validate binding targets of newly discovered radiotracers. The purpose of this study was to correlate quantification of autoradiography signal using the novel next-generation tau positron emission tomography (PET) radiotracer [18F]PI-2620 with immunohistochemically determined tau-protein load in both formalin-fixed paraffin-embedded (FFPE) and frozen tissue samples of patients with Alzheimer's disease (AD) and Progressive Supranuclear Palsy (PSP). Methods: We applied [18F]PI-2620 autoradiography to postmortem cortical brain samples of six patients with AD, five patients with PSP and five healthy controls, respectively. Binding intensity was compared between both tissue types and different disease entities. Autoradiography signal quantification (CWMR = cortex to white matter ratio) was correlated with the immunohistochemically assessed tau load (AT8-staining, %-area) for FFPE and frozen tissue samples in the different disease entities. Results: In AD tissue, relative cortical tracer binding was higher in frozen samples when compared to FFPE samples (CWMRfrozen vs. CWMRFFPE: 2.5-fold, p < 0.001), whereas the opposite was observed in PSP tissue (CWMRfrozen vs. CWMRFFPE: 0.8-fold, p = 0.004). In FFPE samples, [18F]PI-2620 autoradiography tracer binding and immunohistochemical tau load correlated significantly for both PSP (R = 0.641, p < 0.001) and AD tissue (R = 0.435, p = 0.016), indicating a high agreement of relative tracer binding with underlying pathology. In frozen tissue, the correlation between autoradiography and immunohistochemistry was only present in AD (R = 0.417, p = 0.014) but not in PSP tissue (R = −0.115, p = n.s.). Conclusion: Our head-to-head comparison indicates that FFPE samples show superiority over frozen samples for autoradiography assessment of PSP tau pathology by [18F]PI-2620. The [18F]PI-2620 autoradiography signal in FFPE samples reflects AT8 positive tau in samples of both PSP and AD patients.